PENGARUH BRAND EQUITY DAN CUSTOMER VALUE TERHADAP CUSTOMER SATISFACTION RUMAH SAKIT - Sujani Sujani; I Edhy Harjoko (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2014)
Hospital as the provider of health service, should be well managed to improve the quality of service and the quantity of patient. The existence of hospitals both private and government-owned causes intense competition in providing the best health care services. Patients’ satisfaction occurs when their needs, desires and hopes can be fulfilled. To implement this, the hospital should hold a good relationship with patients. Factualy health services remains a complex problem. The complexity of the problem, arise along with the development of medical technology, the increasing socio-economic, educational, and public knowledge about health. This research is intended to find out the effect of brand equity and customer value on customer satisfaction RSUD Bhakti Dharma Husada Surabaya. Research’s approach is quantitative approach. The data were collected by taking sample of population were 111.443, using sampling purposive. From questionnaires that were distributed to 110 respondents and those who met the requirement for sample were 100 respondents. The result was: (1) brand equity has a positive and significant effect on customer satisfaction; (2) customer valuehas a positive and significant effect on customer satisfaction.